History of economic ideas in 20 talks - Lai, Cheng-chung; Ho, Tai-kuang 1969- (Springer, 2002)
Fun and Useful -- Welcome! -- Dead Men’s Wrong Ideas? -- Pioneers and Contenders -- Wealth and Power: Mercantilism -- The Physiocrats and Law of Nature -- Classical School -- Adam Smith and the Invisible Hand of the Market Mechanism -- Thomas Malthus and Effectual Demand -- David Ricardo and Differential Rent -- John Stuart Mill and the Peak Time of the Classic School -- The Rise of Socialism -- Antagonists to the Classic School -- Karl Marx and the Collapse of Capitalism -- Marginal Analysis -- The Marginal School in France -- The Marginal School in Germany, Austria, and the U.K -- Application and Extension of the Marginal School -- Alfred Marshall and the Foundation of the Neo-Classical School -- Theories of Imperfect Competition -- Contemporary Trends -- The Boom of Mathematical Economics -- The Institutional School -- Keynes and Keynesian Economics -- Early Austrian School -- The Rise of the Chicago School -- Epilogue: Economic Ideas in Retrospect -- Further Readings.